2002
DOI: 10.1530/eje.0.1460241
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of ghrelin on insulin and pancreatic somatostatin secretion

Abstract: Objective: Ghrelin is a 28 amino acid residue peptide identified in both human and rat stomach and which acts as an endogenous ligand for the GH secretagogue receptor (GHS-R) and stimulates GH release. GHS-Rs are expressed in a number of tissues, including the pancreas, and ghrelin-like immunoreactivity is present in peripheral plasma, where its levels increase during fasting and decrease after food intake. The relationship between nutritional status and circulating ghrelin concentrations prompted us to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
148
2
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(171 citation statements)
references
References 22 publications
12
148
2
9
Order By: Relevance
“…Second, we have demonstrated that, in two mouse models, an early block in the differentiation of insulin-producing ␤ cells leads to an enormous increase in ghrelin-producing cells, perhaps through a cell fate switch. Although the physiological role of ghrelin remains controversial, several studies have demonstrated that ghrelin functions to regulate insulin activity (28)(29)(30). Therefore, it is remarkable to find a genetic link between these two hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we have demonstrated that, in two mouse models, an early block in the differentiation of insulin-producing ␤ cells leads to an enormous increase in ghrelin-producing cells, perhaps through a cell fate switch. Although the physiological role of ghrelin remains controversial, several studies have demonstrated that ghrelin functions to regulate insulin activity (28)(29)(30). Therefore, it is remarkable to find a genetic link between these two hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin has been reported to induce Antisteatotic effect of daidzein M-H Kim et al hyperglycemia and inhibits the release of insulin from b-cells in mice. 58,59 The hypolipidemic action of daidzein might be partially because of reduction of lipid absorption. Recent data showed that the fermented soygerm isoflavones (daidzein, genistein and glycitein) significantly inhibited pancreatic lipase activity in dose-dependent manner, thereby suppressing absorption of excessive lipid into a body.…”
Section: Discussionmentioning
confidence: 99%
“…An insulinostatic function of endogenous ghrelin within islets has been suggested [13,15,17,[29][30][31]. It was also recently shown to exert inhibitory effects on expression and production of inflammatory cytokines [32] and to attenuate the development of acute pancreatitis in rats by reducing inflammatory infiltrates of pancreatic tissues [33].…”
Section: Discussionmentioning
confidence: 99%